HUBUNGAN ANTARA PENGETAHUAN, PEMBINAAN KADER DALAMANYA MENIADI KADER DENGAN KEAKTIFAN KADER DALAM KEGIATAN POSYANDU DI DESA BABELAN KOTA WILAYAH KERJA PUSKESMAS BABELAN I KABUPATEN BEKASI - Sri Dinengsih; Tati Hartati (Jurnal Kesehatan, 2017)
The activeness of posyandu cadres nationally up to 2011 only reached 78% of the target 80% Posyandu As a community-based health service unit, the movement is run by elected cadres from their own areas who are trained and skilled to carry out routine activities in Posyandu or outside the open posyandu . The success of posyandu can not be separated from the hard work of cadres who volunteer to manage posyandu in their respective areas. The role of cadres is very important in achieving the national health targets because health is a common property and requires cooperation from various cross sectors and programsThe research aims to determine the relationship between knowledge, coaching and the length of time to become a cadre with the activeness of cadres in posyandu activities. This research was conducted in the village of babelan city of working area of ​​puskesmas babelan I district of bekasi started from April to May 2016. This research use observational design with cross sectional approach method. With secondary and primary data. The sample of this study is the cadres registered in the work area of ​​puskesmas babelan I amounted to 109 respondents. Data processing techniques and analysis of this research using statistics with SPSS 18 software applications with Chi Square statistical test and presented in tabular and textual form. The result of this research shows that there is a significant correlation between the knowledge variables with the activeness of the cadres with the result of P value 0,000, the cadre coaching variables are related to the liveliness of the cadres with P value of 0.005, and the variable becomes the cadre is not related to the liveliness of the cadre with P value 0.460. Cadres needed cadres, refreshing about the importance of posyandu activities in the community as an effort to empower the community. Award for cadres who have long been a cadre.